Influence of Neuroticism on Depressive Symptoms Among Chinese Adolescents: The Mediation Effects of Cognitive Emotion Regulation Strategies - Liu, Chengwei; Chen, Liang; Chen, Sanmei (Frontiers in Psychiatry, 2020)
Objective This study aims to explore the multilevel mediation effects of cognitive emotion regulation strategies (CERS) on the link between neuroticism and depressive symptoms among Chinese adolescents. Method A total of 1,265 Chinese adolescents were surveyed using the Chinese version of the Cognitive Emotion Regulation Questionnaire (CERQ-C), the neuroticism scale of the Chinese children’s version of the Eysenck Personality Questionnaire (EPQ-Ck), and the Chinese Children’s Depressive symptoms Inventory (CDI-C). Partial correlation analyses, multigroup confirmatory factor analyses, and structural equation modeling were used. Results (1) Neuroticism had significant, positive correlations with maladaptive CERS strategies (self-blame, acceptance, rumination, catastrophizing, and other-blame) and depressive symptoms (ps < 0.001). Adaptive CERS strategies (positive refocusing, refocus on planning, positive reappraisal, and putting into perspective) had significant, negative correlations with neuroticism and depressive symptoms (ps < 0.001). (2) Neuroticism and CERS strategies significantly predicted depressive symptoms. CERS strategies played partially mediating roles in the relationship between adolescents’ neuroticism and depressive symptoms. Conclusion CERS strategies have partial multilevel mediation effects on the link between neuroticism and depressive symptoms.